2022
DOI: 10.1039/d2cp02164a
|View full text |Cite
|
Sign up to set email alerts
|

An ab initio kinetics study on 2-methyl-2-butanol oxidation induced by ˙OH radicals

Abstract: High-level ab initio calculations were performed to investigate the kinetics of the important initial steps of 2-methyl-2-butanol (2M2B) oxidation. Hydrogen-atom abstraction reactions by hydroxyl (ȮH) radical, water elimination reactions of...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 52 publications
3
7
0
Order By: Relevance
“…13 and 14 shows the comparison of the calculated rate constants in this paper and the data in the literature for the same reaction pathways. It is clear that the rate constants of 2-methyl-2-butanol radicals in this work are in good agreement with those reported by Guo et al 23 while the rate constants from this work are slightly faster than those reported by Guo et al in the low-temperature range. The calculation method used in this paper is similar to that employed by Guo et al 23 The reason for such a small discrepancy may be due to the different parameter settings in MESS input files, such as WellCutoff, GlobalCutoff, etc.…”
Section: Resultssupporting
confidence: 92%
See 3 more Smart Citations
“…13 and 14 shows the comparison of the calculated rate constants in this paper and the data in the literature for the same reaction pathways. It is clear that the rate constants of 2-methyl-2-butanol radicals in this work are in good agreement with those reported by Guo et al 23 while the rate constants from this work are slightly faster than those reported by Guo et al in the low-temperature range. The calculation method used in this paper is similar to that employed by Guo et al 23 The reason for such a small discrepancy may be due to the different parameter settings in MESS input files, such as WellCutoff, GlobalCutoff, etc.…”
Section: Resultssupporting
confidence: 92%
“…It is clear that the rate constants of 2-methyl-2-butanol radicals in this work are in good agreement with those reported by Guo et al 23 while the rate constants from this work are slightly faster than those reported by Guo et al in the low-temperature range. The calculation method used in this paper is similar to that employed by Guo et al 23 The reason for such a small discrepancy may be due to the different parameter settings in MESS input files, such as WellCutoff, GlobalCutoff, etc. Rate constant comparison between this work and the work conducted by Tang et al , 13 as shown in Fig.…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…The pyrolysis and oxidation of many alcohols including the isomers of butanol and some pentanol isomers have been studied due to their potential as “next generation” biofuels. The high-temperature dissociation kinetics and mechanism of the most highly branched pentanol isomer, 2,2-dimethyl­propan-1-ol (neopentanol), do not appear to have been studied. However, the recombination reaction of tert -butyl and hydroxymethyl radicals yielding neopentanol was studied theoretically by Zhao et al and the rate coefficient was estimated by Tsang .…”
Section: Introductionmentioning
confidence: 99%